2013
DOI: 10.1371/journal.pone.0064881
|View full text |Cite|
|
Sign up to set email alerts
|

Decline in Sexual Risk Behaviours among Young People in Zambia (2000–2009): Do Neighbourhood Contextual Effects Play a Role?

Abstract: ObjectiveThis study examined trends in premarital sex, multiple partnership and condom use among young people (15–24 years) in Zambia from 2000 to 2009, and assessed the effects of individual and neighbourhood variables on these sexual behaviour indicators in 2000 and 2009.MethodologyWe analysed data from the Zambia Sexual Behaviour Survey, conducted in 2000, 2003, 2005 and 2009. Multi-stage cluster sampling was used to select 385 neighbourhoods, giving a population sample of 6,500 young people. Using linear-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…A psychometric assessment of Zambian OVC’s HIV risk found prevalent (50%) sexual risk behaviors ( Kane et al, 2018 ), but did not identify factors associated with specific sexual outcomes. Other studies of youth sexual behavior in Zambia have similarly reported suboptimal trends in condom use and early sex ( Kayeyi et al, 2013 ; Ndongmo et al, 2017 ), but these results may have limited generalizability to OVC.…”
Section: Introductionmentioning
confidence: 83%
“…A psychometric assessment of Zambian OVC’s HIV risk found prevalent (50%) sexual risk behaviors ( Kane et al, 2018 ), but did not identify factors associated with specific sexual outcomes. Other studies of youth sexual behavior in Zambia have similarly reported suboptimal trends in condom use and early sex ( Kayeyi et al, 2013 ; Ndongmo et al, 2017 ), but these results may have limited generalizability to OVC.…”
Section: Introductionmentioning
confidence: 83%
“…44 This condition affects the behavior of Indonesian teenagers today, especially sexual behavior. The surrounding environment, which previously served as social control, 45 cannot prevent adolescents from against the norm. Furthermore, peer pressure has a more significant influence on adolescent sexual intentions comparing social-environmental standards.…”
Section: Discussionmentioning
confidence: 99%
“…Residing in urban areas influenced H-RSB positively in Nigeria, Uganda, and Zambia. Kayeyi et al [ 37 ] is of the view that people who live in urban areas are highly likely to have comprehensive knowledge about HIV because they have been largely exposed to mass media and the availability of resources (access to condoms). These encourage them to desist from activities that will increase the risk of infection.…”
Section: Discussionmentioning
confidence: 99%